The Gender Labor Productivity Gap across Informal Firms - Islam, Asif M.; Amin, Mohammad (World Bank, Washington, DC, 2022)
This study uncovers a gender labor productivity gap among informal firms in 14 developing economies. The results show that labor productivity is approximately 15.2 percent (or 0.165 log point) lower among women-owned than men-owned informal firms. Decomposition techniques reveal several factors that contribute to lower labor productivity of women-owned informal firms relative to men-owned informal firms. These include lower education, lower experience, lower capitalization, and less protection from crime among women owners than men owners of informal firms. However, the smaller size of the women-owned firms and their greater return from producing or selling under contract and from security payments narrows the productivity gap. The results provide several specific and general policy recommendations for improving the labor productivity of women-owned informal firms and closing the gap with male-owned informal firms. For one, a substantial amount of the productivity gap can be closed by providing more resources to women such as education, managerial experience, and physical capital. The study also provides some preliminary results on another important policy objective —the costs and benefits of formalization as perceived by women-owned versus men-owned informal firms.